Ἒρως, sexualidad y uniones institucionalizadas: reglas de la ética sexual en la Grecia clásica (Argos, 2025)
In this article, we propose to explore the complex web of meanings that classicalGreek culture developed around ἔρως based on the moral and legal rulesestablished for marriage and pederasty. We aim to demonstrate how the ancientGreeks problematized erotic bonds based on certain assumptions related to thepositive, organizing, and creative power, as well as the negative, chaotic, anddestructive power of ἔρως.
Keywords: ἔρως; marriage; pederasty; rules; moral